2020
DOI: 10.1344/der.2020.37.172-194
|View full text |Cite
|
Sign up to set email alerts
|

Technology adoption in Malaysian schools: An analysis of national ICT in education policy initiatives

Abstract: Educational change, particularly change involving the adoption of educational innovations, is a complex process. In Malaysia, the significant role of information and communication technologies (ICTs) in promoting digital education is reflected in the national ICT in education policy. Nevertheless, studies in the Malaysian educational context have shown that the policy implementation resulted in varying degrees of success. Through a discourse analysis approach, this paper aims to examine the evaluation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Other studies supporting the strength of technology have shown the importance of integrating technology and face to face instructions may augment students' engagement in their learning [4] [6]. The use of technology in the education sector especially in public schools is inevitable, aligned with 21 st -century learning encompassing attitudes, and aspirations in line with the global wave of modernization in education [9]. They elaborated that in Malaysia the use of technology in education started in 1997 as part of the Multimedia Super Corridor's Flagship Applications with the introduction of a smart school project, implemented to develop and equip students with skills to face challenges of the 21 st century before entering the workforce.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Other studies supporting the strength of technology have shown the importance of integrating technology and face to face instructions may augment students' engagement in their learning [4] [6]. The use of technology in the education sector especially in public schools is inevitable, aligned with 21 st -century learning encompassing attitudes, and aspirations in line with the global wave of modernization in education [9]. They elaborated that in Malaysia the use of technology in education started in 1997 as part of the Multimedia Super Corridor's Flagship Applications with the introduction of a smart school project, implemented to develop and equip students with skills to face challenges of the 21 st century before entering the workforce.…”
Section: Literature Reviewmentioning
confidence: 99%
“…(Hussain et al, 2021;Satiakumar et al, 2022;Senan et al, 2017). As a result, it is strongly advised to adopt assistive technology to promote technology-based approach in teaching and learning practices in Malaysia, as stated by Zainal and Zainuddin (2020).…”
Section: Introductionmentioning
confidence: 99%
“…Where educational gamification is concerned, there have not been any governmental policies related to it. However, Zainal and Zainuddin (2020) stated that there have been many digital education initiatives made by the government, with varying success. In due time, it might be a possibility to see attempts made at a national level gamification-based education policies.…”
Section: Introductionmentioning
confidence: 99%